PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS CONTEXTUAL TEACHING AND LEARNING DI LINGKUNGAN SEKOLAH PADA MATA PELAJARAN IPA KELAS III SD MUHAMAMDIYAH PAKEL PROGRAM PLUS YOGYAKARTA - P, Brahmantara Ihsan; Hidayat, Panji (universitas Ahmad Dahlan, 2018)
The research background is caused by students tend to feel bored when learning science. This study aims to develop LKS teaching materials based on Contextual Teaching and Learning in the school environment for science subjects for grade III elementary school, and to determine the feasibility of LKS teaching materials based on Contextual Teaching and Learning developed. This study uses the Research and Develpoment (R & D) method which was adapted from Sugiyono's research. The teaching materials developed through media expert validation, material expert validation, and learning expert validation. Then it was tested at Pakel Muhammadiyah Elementary School Yogyakarta Plus Program by using small group and large group trials. The research was carried out in accordance with the planned steps, in accordance with the development model adapted from Sugiyono's research, resulting in Contextual Teaching and Learning-based LKS teaching materials in the school environment on science subjects material for maintaining environmental health around class III SD Muhammadiyah Pakel Plus Program Yogyakarta, learning can be more effective. The evaluation data for teaching materials developed are as follows: media experts get a percentage of 93.3% in very decent criteria, material experts get a percentage of 81.67% in very feasible criteria, learning experts get a percentage of 80% in eligible criteria, small group trials the percentage of 91.1% is very feasible, the large group trial gets a percentage of 97.82% which is very feasible, the assessment of the small group trial teacher gets a percentage of 98.3% and is very feasible, and the assessment of large group testing teachers get a percentage of 100% which is very feasible. Based on these data, LKS teaching materials based on Contextual Teaching and Learning developed are appropriate for use in the learning process.